(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
This study aims to explore the impact of contextual Arabic language learning within the pesantren environment, focusing on the development of reading (maharah qirā’ah) and speaking (maharah kalām) skills at the Madrasah Aliyah level. Using a qualitative research approach, data were collected through classroom observations, semi-structured interviews, and students’ reflective journals. The findings indicate that the implementation of contextual teaching strategies such as the use of pesantren-based daily themes, situational dialogues, and visual media significantly enhanced students’ engagement, comprehension, and vocabulary retention. Students demonstrated improved ability to connect vocabulary to lived experiences and increasingly used Arabic in everyday social contexts. These results support constructivist language teaching frameworks and highlight the importance of cultural relevance and experiential learning in Arabic education. The study recommends integrating contextual approaches into pesantren curricula to foster more meaningful, effective, and sustainable Arabic language learning.